A highly selective fluorescent sensor for zinc ion based on quinoline platform with potential applications for cell imaging studies. (7th July 2015) - Pradhan, Ankur Bikash; Mandal, Sushil Kumar; Banerjee, Saikat; Mukherjee, Abhishek; Das, Suman; Khuda Bukhsh, Anisur Rahman; Saha, Amrita
Graphical abstract: An 8-aminoquinoline based fluorescent Zn 2+ sensor, 2-methoxy-6-((quinolin-8-ylimino)methyl)phenol (HL ), was synthesized. It has been found to display quick responses through fluorogenic properties on selective 2:1 binding to Zn 2+, as delineated by absorption and fluorescence titrations as well as by Job's method and X-ray crystallography studies. This probe features visible light excitation (461 nm) and emission (594 nm) profiles, excellent selectivity responses for Zn 2+ over other competing biological metal ions with high binding constant and about 17-fold enhancement in fluorescence quantum yield ( Φ ) upon half equivalent of Zn 2+ binding under physiological pH window. The low detection limit in micromolar range (1.3 × 10 −7 M) for Zn 2+, makesHL a suitable candidate for the development of a potential probe. It also exhibits cell permeability and intracellular Zn 2+ sensing in HeLa cells from human cervical cancer cell and rat hippocampal slices. Abstract: An 8-aminoquinoline based fluorescent Zn 2+ sensor, 2-methoxy-6-((quinolin-8-ylimino)methyl)phenol (HL ), was synthesized. It has been found to display quick responses through fluorogenic properties on selective 2:1 binding to Zn 2+, as delineated by absorption and fluorescence titrations as well as by Job's method and X-ray crystallography studies. This probe features visible light excitation (461 nm) and emission (594 nm) profiles, excellent selectivity responses for Zn 2+ over other competing biological metal ions with high binding constant and about 17-fold enhancement in fluorescence quantum yield ( Φ ) upon half equivalent of Zn 2+ binding under physiological pH window. The low detection limit in micromolar range (1.3 × 10 −7 M) for Zn 2+, makesHL a suitable candidate for the development of a potential probe. It also exhibits cell permeability and intracellular Zn 2+ sensing in HeLa cells from human cervical cancer cell and rat hippocampal slices.